Node.js based remote control of thermo-optical plant - Bosak, Tomas; Zakova, Katarina (2015 12th International Conference on Remote Engineering and Virtual Instrumentation (REV), 2015)
The paper demonstrates remote control of the educational laboratory thermo-optical plant. Although this problem has already been addressed several times, there are always new technologies and therefore the approach to the remote experiments gradually changes. In this case the whole application, i.e. both client and server part, was built in JavaScript language and Node.js library.